Study of Torch Outcome on Pregnancy and Fetus in Women with Bod in Duhok Province – Kurdistan Region – Iraq. - Al-Saeed, Adel T.; Abdulmalek, Iman Y.; Ismail, Haifa G. (Science Journal of University of Zakho, 2015)
This study included the distribution of TORCH (T. gondii, Rubella, CMV, and HSV- 2) infections among 276 pregnant women of different ages (18 – 45 years), 184 with Bad Obstetric History (BOH) and 92 with normal obstetric history. All cases were examined serologically by ELISA for the detection of IgG and IgM antibodies against TORCH pathogens. The seropositivity of TORCH infections was significantly higher in women with BOH than those of normal pregnant women with previous normal full term deliveries. As out of 184 pregnant women with BOH, the seropositivity for anti IgG and IgM for T. gondii, CMV, Rubella and HSV-2 were 66 (35.9%) and 6 (3.3%), 159 (86.4%) and 29 (15.8%), 108 (58.7%) and 3 (1.6%) and 104 (56.5%) and 20 (10.9%), respectively. Out of 92 examined normal pregnant women, the seropositivity for anti IgG and IgM for T. gondii, CMV, Rubella and HSV-2 were 38 (41.3%) and one case (1.1%) ,79 (85.9%) and 5 (5.4%), 43 (46.7%),1 (1.1%), and48 (52.2%) and 4 (4.3%), respectively. Regarding age, young ages (25-31 years) showed higher rates of seropositivity, for T.gondii, CMV and HSV-2 which was 57.1% (105/184) than older ages(39-45 years) in which it was only 1.1%  (2/184).except Rubella which showed high seropositivity among all ages. Regarding occupation, housewives showed higher seropositivity(74.3%) than employed women  (40.2%). With respect to period of gestation, for all agents  high infection rates (45.7%) occurred during the first trimester of pregnancy and the  lowest(12.5%)   was recorded in third trimester stages.
Keywords: TORCH; BOD; Age; Occupation; Literacy